Study of 30 cases of histoplasmosis observed in the Mato Grosso do Sul State, Brazil - Chang, Marilene Rodrigues; Taira, Cleison Ledesma; Paniago, Anamaria Melo Miranda; Taira, Deborah Ledesma; Cunha, Rivaldo Venâncio; Wanke, Bodo (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
Thirty cases of histoplasmosis observed at the University Hospital of the Federal University of Mato Grosso do Sul (HU-UFMS) from January 1998 to December 2005 are reported. Most (83.3%) of the patients were men, average 33.4 years old, 63.3% of them were born and living in Mato Grosso do Sul and 83.3% presented AIDS as an underlying disease. In almost all cases (96.7%) the disease occurred in its disseminated form and the most frequent clinical manifestations were: fever (83.3%), weight loss (70.0%), cough (63.3%), hepatomegaly and splenomegaly (40.0%), and lymph node enlargement (36.7%). The laboratory diagnosis was obtained in 29 patients by isolation of Histoplasma capsulatum from various clinical specimens cultivated in Sabouraud dextrose and brain heart infusion agar and in 16 patients the fungus was observed by direct microscopy of Giemsa-stained smears. The observed mortality was 40%. This is the first report in the literature of the occurrence of histoplasmosis in Mato Grosso do Sul State.